The «Anti-steps» method in the rehabilitation program for individuals with various forms of chemical dependence - Butylina, Olena; Kryvoruchko, Dmytro (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2024)
The relevance of the study of the improvement directions of the rehabilitation system of individuals with different forms of chemical dependence is due to the tendency of constant quantitative increase of this category, especially against the background of economic instability, war and limited state support programs in Ukraine. The article attempts to rethink the traditional and recognized program for addicts «12 steps» through the prism of anti-steps and anti-reading methods. The method «Anti-steps» is defined as an alternative approach, which focuses on the circumvention of psychological protective mechanisms that block the rehabilitation process: denial, rationalization, projection, minimization of the problem, avoidance of responsibility. The aim of the article was to identify these mechanisms and form practical tools to overcome them. The author analyzed the basic principles of the 12-step program, substantiated the difficulties of perception of the provisions of this program by the rehabilitators and defined ways of its interpretation through antisteps. It is proven that the «Anti-steps» method can become an alternative approach in rehabilitation programs for addicts. The article presents the preliminary results of the use of the «Anti-steps» method in working with individuals who have various forms of chemical dependence and are undergoing a rehabilitation course based on the network of rehabilitation centers of the public organization «Restart+», as well as assessments and impressions of the rehabilitators obtained by interviewing. It was noted that the «Anti-steps» method allows to relieve tension, leads to a deeper awareness of their behavior by the rehabilitation and overcoming his internal barriers. The author concludes about the expediency and possibility of introducing the «Anti-steps» method to increase the effectiveness of rehabilitation, outlines the next steps of the research in this direction.